2016
DOI: 10.11591/ijece.v6i4.pp1522-1528
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Rectifying Antenna Circuit for Wireless Power Transmission System Operating At ISM Band

Abstract: This paper introduces an overview of a rectifying antenna (rectenna) circuit topology for microwave power transmission system. Specially, a rectenna based on a microstrip patch antenna and a microwave double voltage rectifier at 2.45GHz were designed and fabricated.  The antenna’s return loss is achieved of -15 dB at 2.45GHz. The microwave to DC conversion efficiency of the rectenna was measured as 71.5% with 22 dBm input power and 810 Ohm load. The design  and simulated results  were  carried out  by  the  mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In [24] , a 2.4 GHz rectenna comprising of a combination of a microstrip patch antenna, stepped impedance filter, and zero-biased rectifier is proposed. The authors in [51] demonstrated their microstrip patch rectenna capability in achieving 40.1% efficiency. In [54] , the authors achieved a 3.6 dBi antenna gain with 37.80% WPT efficiency using a microstrip rectenna.…”
Section: ) Rectenna Design A) Microstrip Patch Rectennamentioning
confidence: 99%
“…In [24] , a 2.4 GHz rectenna comprising of a combination of a microstrip patch antenna, stepped impedance filter, and zero-biased rectifier is proposed. The authors in [51] demonstrated their microstrip patch rectenna capability in achieving 40.1% efficiency. In [54] , the authors achieved a 3.6 dBi antenna gain with 37.80% WPT efficiency using a microstrip rectenna.…”
Section: ) Rectenna Design A) Microstrip Patch Rectennamentioning
confidence: 99%